2014
DOI: 10.2174/1573403x09666131117131217
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Heart Failure with Preserved Ejection Fraction: 10 Key Lessons

Abstract: Heart failure with preserved ejection fraction (HFpEF) is a common clinical syndrome associated with high rates of morbidity and mortality. Due to the lack of evidence-based therapies and increasing prevalence of HFpEF, clinicians are often confronted with these patients and yet have little guidance on how to effectively diagnose and manage them. Here we offer 10 key lessons to assist with the care of patients with HFpEF: (1) Know the difference between diastolic dysfunction, diastolic heart failure, and HFpEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 82 publications
3
57
0
2
Order By: Relevance
“…HFpEF can be considered as the new epidemic of the twenty-first century, since the prevalence of this complex clinical syndrome caused by a variety of diseases has remained high or has even increased throughout the last two decades (reviewed in [6]). Investigation into molecular mechanisms underlying HFpEF has been hampered by lack of relevant and tractable models in animals which could recapitulate phenotypic features of diastolic dysfunction in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HFpEF can be considered as the new epidemic of the twenty-first century, since the prevalence of this complex clinical syndrome caused by a variety of diseases has remained high or has even increased throughout the last two decades (reviewed in [6]). Investigation into molecular mechanisms underlying HFpEF has been hampered by lack of relevant and tractable models in animals which could recapitulate phenotypic features of diastolic dysfunction in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HFpEF have a normal-sized LV, often with signs of a mild hypertrophy, with impaired filling, to different degrees, due to abnormal LV relaxation and increased LV stiffness. While extra-cardiac pathophysiological conditions, such as hypertension, obesity, diabetes mellitus, renal dysfunction, and aging, can contribute to HFpEF development, a maladaptive concentric LV remodeling appears to be the main underlying substrate of impaired diastolic function in patients (recently reviewed in [1][2][3][4][5][6][7]). …”
Section: Introductionmentioning
confidence: 99%
“…32 Differentiation of noncardiac from cardiac causes can be difficult, especially when the clinical symptoms are vague and nondescript, as HF patients commonly report to their anesthesiologist. Shortness of breath, exercise intolerance, and fatigue can have multiple causes, but these symptoms along with findings consistent with signs of HFpEF lead to the diagnosis.…”
Section: Diagnosis Of Hfpefmentioning
confidence: 99%
“…32 Abbreviations: ACC/AHA, American College of Cardiologists and American Heart Association; HF, heart failture; NYHA, New York Heart Association. …”
Section: Figmentioning
confidence: 99%
“…However, a large metaanalysis, including community-based studies and trials, observed lower mortality in HFpEF compared with HFrEF, though survival was still much worse than in people without HF. Among patients hospitalized for HF, the mortality rates are higher but the data are again conflicting as to whether or not the prognosis is different in HFpEF and HFrEF: [12] Among 6076 patients discharged from a Mayo Clinic Hospital in Olmsted County, Minnesota with a diagnosis of decompensated HF over a 15-year period (1987 to 2001), 53 percent had a reduced LVEF and 47 percent had a preserved LVEF. One-year mortality was relatively high in both groups but slightly lower in patients with a preserved LVEF (29 versus 32 percent in patients with reduced LVEF, adjusted hazard ratio 0.96, 95% CI 0.92-1.00).…”
Section: Symptomatic Patients With Hfpef)mentioning
confidence: 99%